Extended treatment of abrocitinib: evaluation of efficacy and safety in chronic actinic dermatitis - Tang, Lu; Zhong, Lanhai; Liang, Liangzi; Han, Jiande; Lin, Naiyu (Frontiers in Medicine, 2026)
IntroductionJAK inhibitors are well-established for their utilization in the treatment of autoinflammatory diseases, with the JAK1 inhibitor abrocitinib primarily employed in the management of atopic dermatitis. To provide new clinical therapeutic experience for patients with chronic actinic dermatitis (CAD), reveal the inflammatory pathways that may be involved in the treatment of CAD with abrocitinib and to provide clues for exploring the pathogenesis of CAD.MethodsIn a 3-month longitudinal study, we recorded and analyzed laboratory test data and clinical severity assessments in 16 patients diagnosed with chronic actinic dermatitis treated with abrocitinib. And the plasma samples of 6 patients before and after treatment were analyzed proteomically using Olink inflammation panel.ResultsAfter 12 weeks of treatment, there was a significant decrease in disease severity scores of 16 patients. No serious adverse events were identified throughout the course of treatment. Significant changes in several inflammatory factors such as EN-RAGE, MCP-3, MCP-4, IL-13, CCL4, FGF21 and TNFRSF9 were observed after treatment.DiscussionThe analysis of our data demonstrates that abrocitinib may be an effective therapeutic option in the management of CAD. IL-13 and CCL-4 might be the core effective factors after the therapy.